The preliminary study on the antifungal effect of Kaffir lime (Citrus hystrix DC) peel extract against Malassezia furfur - Mulyati Sri Rahayu; Nailah Najah; Wizar Putri Mellaratna (International Journal of Secondary Metabolite)
Pityriasis versicolor is one of the most common fungal infections on the skin caused by Malassezia furfur. Kaffir lime fruit (Citrus hystrix DC), especially its peels’ contents in secondary metabolite, may play a healing role against such infections. Therefore, the aim of this study was to determine the antifungal potential of Kaffir lime peel extract against Malassezia furfur. Ethanol extracts of the peels of Kaffir lime were tested for its antifungal properties against Malassezia furfur at different tested concentrations, namely 25%, 50%, 75%, and 100%. Every treatment was performed with 4 replications. Inhibition zone formed surrounding the paper disc measured after 24 hours of incubation using the caliper method. Data were subjected to the Kruskal-Wallis test and the Mann-Whitney Post hoc test. The study revealed that the kaffir lime fruit extract gave a significant effect on the inhibition zone (p< 0.05). The results showed that the higher inhibition zone was found at control group and it was different significantly from other treatments. However, among the tested concentrations, the best treatment was detected at a concentration of 100%, which was significantly different from other concentrations. Kaffir lime peel has an antifungal effect against Malassezia furfur and the best tested concentration was 100%.